1984
DOI: 10.1002/ajmg.1320170126
|View full text |Cite
|
Sign up to set email alerts
|

X‐linked mental retardation associated with bilateral clasp thumb anomaly

Abstract: We report on a family in which mental retardation is associated with a bilateral clasp-thumb anomaly (absent extensor pollicis brevis tendons). Males over 3 generations were documented to have this combination of findings and pedigree analysis strongly suggests X-linked inheritance. We are not aware of previous reports of X-linked mental retardation (XLMR) associated with this anomaly. There was no evidence of a fragile X in the 2 brothers who were studied for this abnormality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…The Spanish connotation reminds us that 21/41 patients are known to be Mexican-American; the photograph published by Gareis and Mason [1984] in their report of affected half-brothers from California also suggests Hispanic origin. Rewards of genetic counseling for this condition are considerable since families may be extensive and linkage to DNA markers at Xq28 allows carrier detection and prenatal diagnosis.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The Spanish connotation reminds us that 21/41 patients are known to be Mexican-American; the photograph published by Gareis and Mason [1984] in their report of affected half-brothers from California also suggests Hispanic origin. Rewards of genetic counseling for this condition are considerable since families may be extensive and linkage to DNA markers at Xq28 allows carrier detection and prenatal diagnosis.…”
Section: Discussionmentioning
confidence: 85%
“…Observation of 5 additional families [Gareis and Mason, 1984 Winter et al, 1989;SchranderStumpel et al, 1990;Rietschel et al, 19911 has further established this entity and suggested linkage to the Xq28 region.…”
Section: Bianchine and Lewismentioning
confidence: 84%
“…We think that sufficient evidence exists from the families described by Bianchine and Lewis (19741, Gareis and Mason (1983) and our family to conclude on the existence of a distinct XLMR-clasped thumb syndrome, cephaly was documented only in the family reported by Bianchine and Lewis (1974), patients in the other 2 families had head curcumferences below the 50th centile in each case. The manifestations of this condition overlap with those of X-linked hydrocephalus from aqueductal stenosis.…”
Section: Discussionmentioning
confidence: 68%
“…Bianchine and Lewis (1974) reported a family with XLMR, microcephaly, growth retardation, exaggerated lordosis and adducted thumbs, Our family and that of Gareis and Mason (1983) contain no known cases of microcephaly. Testicular size of our patients is normal, marker-X is absent, and no evidence of hydrocephalus is seen on CT scan.…”
Section: Discussionmentioning
confidence: 96%
“…This clinical assessment was confirmed by the presence of recombination with 'an HPRT polymorphi& (Z=-1.8 at e=O.OO) in our family which was shown to be linked to the disease locus in the Pettigrew family (2=2.13 at e=O.OO) by Huang et al [ 19901. Finally, the comparison with MASA syndrome (Fig. 1) [Bianchine and Lewis, 1974;Gareis and Mason, 1984;Kenwrick et al, 1986;Winter et al, 19891 shows striking phenotypic differences.…”
Section: Discussionmentioning
confidence: 97%